2018
DOI: 10.1111/cas.13403
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin suppresses proliferative and metastatic potential by downregulating transforming growth factor‐β‐induced expression in urothelial carcinoma

Abstract: Transforming growth factor‐β‐induced (TGFΒI) is considered to be a vital gene in several carcinomas. In this study we determined the effect of TGFBI on the proliferative and metastatic potential of human urothelial carcinoma (UC) cells as well as its mRNA and protein expression, which were detected by RT‐PCR and western blot, respectively. UC cell proliferation was analyzed by WST‐1 assay and Hoechst 33258 staining. The effect of TGFBI on UC cell metastasis was analyzed using adhesion, migration and invasion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…In line with these observations, we showed a tumor promoting function of TGFBI in bladder cancer in vitro, in terms of enhanced cell proliferation and migration. Our results are further supported by a study from Shang and colleagues, who demonstrated in RT112 and 253J bladder cancer cell lines [40], that siRNA-mediated low TGFBI expression significantly decreased proliferation, adhesion, migration and invasion. In contrast, overexpression of TGFBI in these bladder cancer cells significantly enhanced all those cellular functions.…”
Section: Discussionsupporting
confidence: 89%
“…In line with these observations, we showed a tumor promoting function of TGFBI in bladder cancer in vitro, in terms of enhanced cell proliferation and migration. Our results are further supported by a study from Shang and colleagues, who demonstrated in RT112 and 253J bladder cancer cell lines [40], that siRNA-mediated low TGFBI expression significantly decreased proliferation, adhesion, migration and invasion. In contrast, overexpression of TGFBI in these bladder cancer cells significantly enhanced all those cellular functions.…”
Section: Discussionsupporting
confidence: 89%
“…Binding of collagen to integrin is mediated by TGFBI 35. In addition, TGFBI can activate matrix metalloproteinase (MMP) secretion and promote invasion 36. We found that silencing COL1A1 down-regulated the expression levels of TGFBI and MMP9.…”
Section: Resultsmentioning
confidence: 86%
“…These include TGF‐β signaling [ 37 ]. TGFβI is an ECM protein functionally linked to fibronectin [ 38 ], as it serves as a linker protein that mediates integrin binding to extracellular proteins, such as fibronectin, collagen, and laminins [ 39 ]. Epithelial OC cells have the potential to switch between epithelial and mesenchymal states during metastasis, and previous findings showed that the TGFβI signaling significantly impacts epithelial‐to‐mesenchymal transition and promotes the malignant potential of OC spheroid cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%